Analisis Risiko Bisnis (Studi Kasus Kedai Kopi) - Andika Kristianto; Muhammad Frasha Candra P; Muhammad Khabib Ikhwanudin; Nathanael Distri Roni Christian; Ledjar Nugroho (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
In other words, coffee is one of the most popular drinks. Indonesian coffee production is increasing quite rapidly. In 2022, coffee production will reach around 632 thousand tons, up 0.74 percent, and in 2023, it will increase by around 636.7 thousand tons. Robusta and Arabica coffee are the most diverse types of coffee, and have various forms of coffee beans. Traders and wholesalers It is expected that a software that can be applied to help distinguish types of coffee based on the shape of the coffee beans to prevent mistakes in selecting coffee beans. The risk identification process is the first step in coffee shop business risk management. Potential risks need to be identified, such as changes in customer tastes, fluctuations in the price of coffee raw materials, intense competition, regulatory changes, and supply shortages.